2016
DOI: 10.1002/mrd.22686
|View full text |Cite|
|
Sign up to set email alerts
|

Endometrial breakdown with sustained progesterone release involves NF-κB-mediated functional progesterone withdrawal in a mouse implant model

Abstract: Irregular uterine bleeding is a major side effect of long-acting progestogen-only contraceptives in women, and is the primary reason women discontinue their use. In this study, a mouse model of endometrial breakdown was established using a subcutaneous progesterone implant to understand how irregular bleeding begins. Although progestogens sustained decidualization, endometrial breakdown was still observed in this model. We, therefore, hypothesized that endometrial breakdown might involve functional progesteron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…67 A recent study suggested that repression of PGR by NF-κB p65 may mediate functional progesterone withdrawal in a mouse model. 68 Strikingly, in human DSCs a co-immunoprecipitation time series revealed that NF-κB p65 and PGR interaction is strongest during late decidulization. 68 Thus, in the early phase, PGR-induced NFκBIα and GILZ may act as a sink and exhaust a considerable proportion of free NF-κB p65.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…67 A recent study suggested that repression of PGR by NF-κB p65 may mediate functional progesterone withdrawal in a mouse model. 68 Strikingly, in human DSCs a co-immunoprecipitation time series revealed that NF-κB p65 and PGR interaction is strongest during late decidulization. 68 Thus, in the early phase, PGR-induced NFκBIα and GILZ may act as a sink and exhaust a considerable proportion of free NF-κB p65.…”
Section: Discussionmentioning
confidence: 98%
“…68 Strikingly, in human DSCs a co-immunoprecipitation time series revealed that NF-κB p65 and PGR interaction is strongest during late decidulization. 68 Thus, in the early phase, PGR-induced NFκBIα and GILZ may act as a sink and exhaust a considerable proportion of free NF-κB p65. As the levels of NFκBIα and GILZ decrease in progressed DSCs, this repression is subsequently relieved, and free NF-κB p65 may repress PGR and prime functional progesterone withdrawal.…”
Section: Discussionmentioning
confidence: 98%
“…After treatment with SDHD, the content of progesterone was significantly higher than that of the model group. It was indicated that SDHD can increase the progesterone and then acts through the PGR to regulate changes in endometrial tissue [36]. In the screening of network pharmacology pathways, we found that PGR is mostly involved in molecular function in GO analysis, such as steroid binding, sequence-specific DNA binding, steroid hormone receptor activity, transcription factor activity, transcriptional activator activity, RNA polymerase II core promoter proximal region sequence-specific binding, and Zinc ion binding.…”
Section: Animal Experiments To Verify the Efficacymentioning
confidence: 86%
“…PGR, progesterone receptor, is an intracellular protein that is activated by the steroid hormone progesterone. Progesterone, acting through the PGR, is one of the most critical regulators of endometrial differentiation and helps regulate the cyclic changes in endometrial tissue [36,37]. Related studies have found the gene network that operates downstream of each PGR isoform, which contains PGR-A and PGR-B, to mediate critical functions of regulation of the cell cycle and angiogenesis [37].…”
Section: Screened Hub Nodementioning
confidence: 99%
“…The p65 subunit of NF-κB and progesterone receptor (PR) can repress each other through direct contact. The mutual repression of p65 and PR in the endometrium is involved in endometrial biologic alterations during the menstrual cycle and pathophysiologic processes, such as irregular uterine bleeding [38][39][40]. In a study of 109 patients with endometriosis, increased p65 expression and decreased PRB (a PR isoform) expression jointly served as biomarkers for the recurrence of ovarian endometrioma [41].…”
Section: Progesteronementioning
confidence: 99%